Business Plan Frozen Meat Shop Kotak Daging - nur, hanny; Kaniawati , Keni (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2025)
The Central Statistics Agency (BPS) noted that gross domestic product (GDP) at constant prices (ADHK) from the food and beverage industry was IDR 206.9 trillion in the first quarter of 2023. This value grew 5.33% compared to the same period in the previous year (yoy) amounting to IDR 195.75 trillion. Plus developments and changes in people's lifestyles in Indonesia prefer practical, economical, fast, and delicious food. This shows that the growth of the food and beverage industry will continue to grow in the future. This research examines business planning and development opportunities based on aspects of the Timmons model of entrepreneurship, the Business Model Canvas (BMC), and aspects of business feasibility studies, financial, marketing, human resources, and operational aspects, and also examines the opportunities and threats of the food and beverage industry in particular frozen food industry. This business development plan starts based on the criteria of Payback Period, Net Present Value, Profitability Index, and Internal Rate of Return. The research method used is descriptive qualitative with observational data collection techniques. The operational variables used are based on the Timmons model criteria. By mapping the nine elements of BMC, a strategy was obtained that Frozen Meat Shop Kotak Daging provides premium, hygienic, and practical frozen meat by making it easy to get products through delivery services. The results of the research show that the investment for developing the Frozen Meat Shop Kotak Daging business is IDR. 195,985,000 using its funds. Positive NPV of Rp. 877,450,214, IRR 85.83%, NPM 38.87%, and investment payback period of 1 year and 6 months. These results show that the Frozen Meat Shop business development plan for the Kotak Daging is feasible because it can provide high potential profits.